PENGARUH SHOPPING LIFESTYLE DAN HARGA DISKON TERHADAP IMPULSIVE BUYING - Mongilong, Miya Purnama; Hafid, Radia; Maruwae, Abdulrahim; Mahmud, Melizubaida; Toralawe, Yulianti (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2024)
This research aims to determine the influence of Shopping Lifestyle and Discount Prices on Impulsive Buying through TikTok Shop media among Generation Z in Dulalowo Timur Village, Kota Tengah Subdistrict, Gorontalo City. The sampling technique used is purposive sampling, with the sample size determined using the Siovin formula, resulting in 86 respondents. The data collection technique employed in this research is a questionnaire, which was analyzed using multiple linear regression analysis. The results indicate that Shopping Lifestyle and Discount Prices positively and significantly influence Impulsive Buying through TikTok Shop media. The coefficient of determination (R Square) indicates a value of 55.8%. In conclusion, Shopping Lifestyle and Discount Prices simultaneously influence Impulsive Buying through TikTok Shop media, while the remaining 44.2% is influenced by other variables not examined in this research.